ANALISIS PENILAIAN KESEHATAN HUTAN MANGROVE DI KABUPATEN LAMPUNG TIMUR - Yeni Apriliyani; Rahmat Safei; Hari Kaskoyo; Christine Wulandari; Indra Gumay Febryano (Jurnal Hutan Tropis, 2020)
This research was conducted in mangrove forests in Kecamatan Pasir Sakti andKecamatan Labuhan Maringgai in April-June 2019. The stages of this study consisted of observations, interviews with comparative questionnaires (Analytic Hierarchy Process-AHP), making cluster plots to determine the health condition of mangrove forests through forest health monitoring techniques (Forest Health Monitoring-FHM), measurement of forest health, and assessment of forest health. The results of this study indicate that the important indicators of thepriority scale of mangrove forest health indicators in East Lampung Regency are vital indicators (0.4211), site quality (0.2972), biodiversity (0.2282) and productivity (0.0534). The health status of mangrove forests in Kabupaten Lampung Timur varies, starting from good and bad conditions. Good status is in cluster 1 (with a value of 8.92) and cluster 4 (with a value of 8.38), while the bad status is found in cluster 2 (with a value of 3.43) and cluster 3 (with a value of 3.56). The width of each cluster is 4,048.93 m2 so that the health status value of mangroveforests in Kabupaten Lampung Timur is included in the medium category.